European survey on principles of prudent antibiotic prescribing teaching in undergraduate students. (April 2015) - Pulcini, C.; Wencker, F.; Frimodt-Møller, N.; Kern, W.V.; Nathwani, D.; Rodríguez-Baño, J.; Simonsen, G.S.; Vlahović-Palčevski, V.; Gyssens, I.C.; ,
Abstract: We surveyed European medical schools regarding teaching of prudent antibiotic prescribing in the undergraduate curriculum. We performed a cross-sectional survey in 13 European countries (Belgium, Croatia, Denmark, France, Germany, Italy, Netherlands, Norway, Serbia, Slovenia, Spain, Switzerland, United Kingdom) in 2013. Proportional sampling was used, resulting in the selection of two to four medical schools per country. A standardized questionnaire based on literature review and validated by a panel of experts was sent to lecturers in infectious diseases, medical microbiology and clinical pharmacology. In-depth interviews were conducted with four lecturers. Thirty-five of 37 medical schools were included in the study. Prudent antibiotic use principles were taught in all but one medical school, but only four of 13 countries had a national programme. Interactive teaching formats were used less frequently than passive formats. The teaching was mandatory for 53% of the courses and started before clinical training in 71%. We observed wide variations in exposure of students to important principles of prudent antibiotic use among countries and within the same country. Some major principles were poorly covered (e.g. reassessment and duration of antibiotic therapy, communication skills). Whereas 77% of the respondents fully agreed that the teaching of these principles should be prioritized, lack of time, mainly due to rigid curriculum policies, was the main reported barrier to implementation. Given the study design, these are probably optimistic results. Teaching of prudent antibiotic prescribing principles should be improved. National and European programmes for development of specific learning outcomes or competencies are urgently needed.